PENGARUH PENERAPAN METODE RESITASI TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMAN 1 LENGAYANG - Nurman, Oki; Rahmi, Rahmi; Febriana, Rina (Pendidikan Matematika, 2013)
The background of this research was students mathematic concept understanding still less. The purpose of research to know what was understanding of students mathematic concept at class XI IPA SMAN 1 Lengayang that used recitation method more effective than students mathematic concept understanding toward used learning conventional. The type of this research was experimental research with randomly subject. The population of this research were students class XI IPA had registered at 2013/2014. Sample was take randomly, it choose class XI IPA 1 as experimental class and class XI IPA 2 as control class. The instrument used in this research was test with concept indicator understanding in essay with reliability was 0.908. Based on the result of data analysis get mean score of students in experimental class was 77.45 highery then control class was 64.93. From MINITAB result get p-value = 0.000 was smaller than Â = 0.05. So, students mathematic concept understanding that used recitation method better than students mathematic concept understanding with used teaching conventional